The Phenomenon of Bullying in Schools as a Basis for Developing Social Studies Learning Materials - Faujian, Ares; Widiastuti, Anik; Sudrajat, Sudrajat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This qualitative research aims to analyze the phenomenon of bullying in schools to develop social sciences learning materials using literature studies and thematic synthesis. The research method includes collecting secondary literature from various indexed and accredited journals (Google Scholar, ISSN, Sinta, and Scopus), research reports, and credible documents published between 2015 and 2025. The thematic synthesis process includes initial coding, theme development, theme validation, theme naming, and compiling a narrative synthesis. This study has divided its findings into two main categories: 1) Development of Social Studies (IPS) learning materials on bullying in schools, which include the history of bullying, factors causing bullying, various forms of bullying, impacts of bullying, and the basis of contemporary social theory to understand the dynamics of bullying. 2) Strategies for developing Social Studies (IPS) learning materials for bullying prevention that can be implemented through Problem-Based Learning (PBL), strengthening social behavior, integration of Social and Emotional Learning (SEL), and the application of proposed social learning theories to encourage critical reflection and development of student empathy. This study's results provide a reference for Social Studies teachers, curriculum developers, researchers, and policymakers aiming to reduce and prevent bullying through an anti-bullying-focused Social Studies curriculum.